(untitled) (Journal of Astronomy & Earth Sciences Education, 2019)
When judging how important and influential a published article is in a refereed journal, the most important thing one might pay attention to is the evidence-based conclusion and the implications of that conclusion (Slater, 2019). At the same time, another way to judge an article’s influence is by looking at how frequently the article is cited, using a tool such as scholar.google.com: The caveat to high citation numbers being a great measure of importance and value is that sometimes a published paper is highly cited simply because its conclusions are incorrect and many authors are capitalizing on the opportunity to correct its mistaken message (Slater, 2018a). A third important component to a great paper is how well the research is situated in the existing literature landscape - the compulsory literature review. The best papers clearly specify the research question’s space by stating what is known, what is not known, and why the paper in question fills an important gap in the scholarly community’s understanding (Slater, 2018a). What is missing in the most common list of criteria for greatness - conclusions, citations, and situation in the existing literature - is an acknowledgement of the critical importance of the methods section.